Doping in combat sports: a systematic review - Damjanovic, S.; Rossi, C.; Manolopoulos, N.; Matijevic, T.; Korpak, D.; Kurtanovic, A.; Murtin, V.; Stanojevic, M.; Giustino, V.; Roklicer, R.; Bianco, A.; Drid, P. (The Physician and Sportsmedicine, 2025)
Purpose